A contribution to the taxonomy of Anthaxia (Cratomerus) (Coleoptera: Buprestidae: Anthaxiini) of East Africa - Obořil, Martin; Baňař, Petr (Zootaxa, 2021)
Anthaxia (Cratomerus) tankenethi sp. nov. from East Africa is described. New synonymy of A. (C.) gebhardti Obenberger, 1924 (= A. (C.) cytharaea Obenberger, 1931 syn. nov.) is proposed. Redescription of A. (C.) gebhardti is provided. Lectotypes for A. (C.) gebhardti Obenberger, 1924 and A. (C.) cytharaea Obenberger, 1931 are designated.